Effective Versions of Two Theorems of RADO. (17th March 2020) - Bell, Jason; Funk, Daryl; Du Kim, Byoung; Mayhew, Dillon
Abstract: Let M be a representable matroid on n elements. We give bounds, in terms of n, on the least positive characteristic and smallest field over which M is representable.